Mutual Preservation: A Review of Interactions Between Cervicovaginal Mucus and Microbiota - Vagios, Stylianos; Mitchell, Caroline M. (Frontiers in Cellular and Infection Microbiology, 2021)
At mucosal surfaces throughout the body mucus and mucins regulate interactions between epithelia and both commensal and pathogenic microbiota. Although the microbes in the female genital tract have been linked to multiple reproductive health outcomes, the role of cervicovaginal mucus in regulating genital tract microbes is largely unexplored. Mucus-microbe interactions could support the predominance of specific bacterial species and, conversely, commensal bacteria can influence mucus properties and its influence on reproductive health. Herein, we discuss the current evidence for both synergistic and antagonistic interactions between cervicovaginal mucus and the female genital tract microbiome, and how an improved understanding of these relationships could significantly improve women’s health.